2020
DOI: 10.1038/s41433-020-1009-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and refractive error on quick contrast sensitivity function in Chinese adults: a pilot study

Abstract: Purpose To evaluate the potential effect of age and refractive error on visual acuity (VA) performance and quick contrast sensitivity function (qCSF) in normal Chinese adults. Method Ninety-two subjects with normal best corrected distance VA (BCDVA) were enrolled in this pilot study. Measurements included BCDVA, best corrected near VA (BCNVA), unaided VA (UNVA), habitual spectacle-corrected near VA (SCNVA) and qCSF. For analyses, subjects were categorized into three age groups (20~40 years, 41~60 year and >60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
2
15
2
Order By: Relevance
“…1c). In normal eyes, the CS appeared to decrease significantly by 6.0 cpd [12,13], which was different from that in keratoconus as shown in our study. A previous study showed that a CS threshold of 6.0 cpd was closely correlated with patient's ability to identify traffic signs and objects, reflecting the visual function in daily life [3].…”
Section: Discussioncontrasting
confidence: 99%
“…1c). In normal eyes, the CS appeared to decrease significantly by 6.0 cpd [12,13], which was different from that in keratoconus as shown in our study. A previous study showed that a CS threshold of 6.0 cpd was closely correlated with patient's ability to identify traffic signs and objects, reflecting the visual function in daily life [3].…”
Section: Discussioncontrasting
confidence: 99%
“…The study was designed to identify specific macular and peripheral locations where myopes and emmetropes may show differences in CSF. Consistent with Li et al (2020) , we found no contrast sensitivity difference between the emmetropes and myopes in a wide range of SFs in the fovea. However, we found increased contrast sensitivities in the myopia group at the para- (6°) and mid-peripheral (12°) eccentricities.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to the abovementioned, the decline is caused by an increased intraocular lens density, internal reflections and light scatter and a general decrease in retinal illumination [10,107,109,110]. Studies found that a decreased sensitivity manifesting as a difficulty in identifying faces supported the physiological change with finding changes in the visual cortex [10,[109][110][111].…”
Section: Contrast Sensitivitymentioning
confidence: 99%